Neonatal Screening for Congenital Hypothyroidism in Paholpolpayuhasena Hospital - Sagoolngam, Supachatr (Journal of Health Science of Thailand, 2018)
The objective of this retrospective descriptive study was to determine the incidence of congenital hypothyroidism and study case of congenital hypothyroidism in Paholpolpayuhasena hospital from October 1, 2002 to September 30, 2007. A total of 15,862 newborns undergoing neonatal screening for congenital hypothyroidism were carried out and 7 patients were diagnosed with congenital hypothyroidism. The incidence of congenital hypothyroidism in Paholpolpayuhasena hospital was 1 : 2,265 live births, recall rate was 0.35 percent and no patient had clinical presentation of congenital hypothyroidism after treatment and follow up. In conclusion, the neonatal screening program and clinical practice guideline for congenital hypothyroidism was very useful in patient management and prevention of mental retardation.